Experimental and theoretical studies on glucose conversion in ethanol solution to 5-ethoxymethylfurfural and ethyl levulinate catalyzed by a Brønsted acid. Issue 35 (31st August 2021) - Wang, Shijie; Chen, Yihang; Jia, Yu; Xu, Guizhuan; Chang, Chun; Guo, Qianhui; Tao, Hongge; Zou, Caihong; Li, Kai
Abstract : DFT calculations combined with experiments were used to discover the mechanism and reaction pathway of the glucose alcoholysis reaction. Abstract : The fundamental understanding of glucose conversion to 5-ethoxymethylfurfural (EMF) and ethyl levulinate (EL) (value-added chemicals from biomass) in ethanol solution catalyzed by a Brønsted acid is limited at present. Consequently, here, the reaction pathways and mechanism of glucose conversion to EMF and EL catalyzed by a Brønsted acid were studied, using an experimental method and quantum chemical calculations at the B3LYP/6-31G(D) and B2PLYPD3/Def2TZVP level under a polarized continuum model (PCM-SMD). By further verification through GC/MS tests, the mechanism and reaction pathways of glucose conversion in ethanol solution catalyzed by a Brønsted acid were revealed, showing that glucose is catalyzed by proton and ethanol, and ethanol plays a bridging role in the process of proton transfer. There are three main reaction pathways: through glucose and ethyl glucoside (G/EG), through fructose, 5-hydroxymethylfurfural (HMF), levulinic acid (LA), and EL (G/F/H/L/EL), and through fructose, HMF, EMF, and EL (G/F/H/E/EL). The G/F/H/E/EL pathway with an energy barrier of 20.8 kcal mol −1 is considered as the thermodynamic and kinetics primary way, in which the reaction rate of this is highly related to the proton transfer in the isomerization of glucose to fructose. The intermediate HMF was formed from O5 via a ring-opening reaction and by the dehydration of fructose, and was further converted to the main product of EMF by etherification or by LA through hydrolysis. EMF and LA are both unstable, and can partially be transformed to EL. This study is beneficial for the insights aiding the understanding of the process and products controlling biomass conversion in ethanol solution.